The use of e-learning platforms during the Covid-19 movement control order: Malaysian university students’ perceptions, satisfactions, and challenges - Azar, Ali Sorayyaei; Iskandar Tan, Nur Haslinda; AlAqad, Mohammed H.; Hashim, Azirah; Mohd Nor, Nor Fariza; Mehar Singh, Manjet Kaur; Mohamad Ali, Afiza (ASR Research India, 2022)
The sudden increase in the statistical outbreak of Coronavirus in Malaysia had urged the government to impose a movement control order (MCO) starting 18 March 2020 for Malaysians to stay at home to stop the virus from spreading even more. Since the virus had been spreading rapidly across the globe, the situation demanded the closure of schools and educational institutions giving rise to emergency remote teaching in ensuring that students are not neglected during this pandemic. Due to the dramatic changes in all public and private institutions from face-to-face interaction to online learning, students have faced difficulty and challenges in adapting to the online learning methods that were made compulsory by lecturers and institutions’ directives. Thus, this article investigates the students’ perceptions, satisfaction, and challenges during this period of sudden change to e-learning platforms during the Covid-19 Movement Control Order. The questionnaire was piloted with the first 128 responses to analyze the validity and reliability of each item categorically. The reliability statistics on the survey for students’ perceptions showed .896, for challenges faced by the students showed .906, and for the students’ satisfaction showed .910. This article presents further findings gathered from a total of 329 participants that involved 79% from public universities and 21% from private universities across Malaysia. The significant correlations between the students’ perceptions, challenges faced, and satisfaction with their universities’ e-learning platforms were analyzed. Lastly, discussions and three implications demonstrate how participants’ perception, challenges, and satisfaction significantly motivate their cognitive engagement and academic performance.